2004
DOI: 10.1016/j.bandc.2004.02.037
|View full text |Cite
|
Sign up to set email alerts
|

The eyes have it!: An fMRI investigation

Abstract: For the past several years it has been thought that cues, such as eye direction, can trigger reflexive shifts in attention because of their biological relevance and their specialized neural architecture. However, very recently, Ristic, Friesen, and Kingstone (2002) reported that other stimuli, such as arrows, trigger reflexive shifts in attention in a manner that is behaviourally identical to those triggered by eyes. Nevertheless these authors speculated that reflexive orienting to gaze direction may be subser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 3 publications
(4 reference statements)
7
94
3
Order By: Relevance
“…This is consistent with a proposed circuit in which first the cue would be decoded by a specialized mechanism and then the output of this processing would be relayed to a generic attention mechanism, which would reorient the focus of attention (see Corbetta & Shulman, 2002, for a recent review of the possible structural and functional components of attentional orienting). In line with this idea, extant neuroimaging data has revealed links between the superior temporal sulcus (putatively the eye-gaze interpreter) and the posterior parietal cortex, an area critical for orienting attention in space (George, Driver, & Dolan, 2001; also see Kingstone et al, 2004). Interestingly for the interpretation of our results, several neuropsychological (e.g., Làdavas & Farnè, 2004), human electrophysiological (e.g., Kingstone et al, 2004;McDonald, Teder-Sälejärvi, Di Russo, & Hillyard, 2003), and neuroimaging (e.g., Macaluso & Driver, 2004) studies show that the cited attention mechanisms in the parietal cortex are multimodal.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This is consistent with a proposed circuit in which first the cue would be decoded by a specialized mechanism and then the output of this processing would be relayed to a generic attention mechanism, which would reorient the focus of attention (see Corbetta & Shulman, 2002, for a recent review of the possible structural and functional components of attentional orienting). In line with this idea, extant neuroimaging data has revealed links between the superior temporal sulcus (putatively the eye-gaze interpreter) and the posterior parietal cortex, an area critical for orienting attention in space (George, Driver, & Dolan, 2001; also see Kingstone et al, 2004). Interestingly for the interpretation of our results, several neuropsychological (e.g., Làdavas & Farnè, 2004), human electrophysiological (e.g., Kingstone et al, 2004;McDonald, Teder-Sälejärvi, Di Russo, & Hillyard, 2003), and neuroimaging (e.g., Macaluso & Driver, 2004) studies show that the cited attention mechanisms in the parietal cortex are multimodal.…”
Section: Discussionmentioning
confidence: 90%
“…However, this lack of behavioral dissociation does not necessarily imply that eye gaze and other types of cues are processed alike (Kingstone et al, 2000;Kingstone et al, 2004) or even that they always have an equivalent behavioral effect. For instance, Friesen et al (2004) have found that it is harder to attend to the opposite direction of a gaze cue than to that of an arrow cue (also see Kingstone et al, 2000, andRicciardelli, Ro, &, for laterality-based dissociations).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Joint attention has been observed in individuals as young as 3 months (e.g., Scaife & Bruner, 1975) and is thought to be a critical first step in learning social interaction, given that gaze provides important information regarding an individual's interests and intent (e.g., Moore & Dunham, 1995). In adult populations, gaze cues have been shown to lead to reflexive shifts of attention in the direction consistent with gaze (e.g., Bayliss & Tipper, 2006;Driver et al, 1999;Friesen & Kingstone, 1998;Friesen, Ristic, & Kingstone, 2004;Kingstone, Tipper, Ristic, & Ngan, 2004). In the laboratory, these effects are typically demonstrated by presenting a nonpredictive cue at fixation that is a drawing/photograph of a face looking to the left or right.…”
Section: Abstract Gaze Cues Political Temperamentmentioning
confidence: 99%